ความสัมพันธ์ระหว่างบุคลิกภาพแบบวิตกกังวล ความกลัวการถูกประเมินในแง่ลบ ความเพลิน การยอมรับ และ ความวิตกกังวลทางการแสดงละครเวที ในนักแสดงละครเวที - อาภัสสร ผาติตานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purpose of this study was to examine the relationships among trait anxiety, fear of negative evaluation, flow, acceptance, and theatre performance anxiety. Participants were 205 theatre actors, aged between 18-62, who had a role in an official full production of a straight or musical play. Scene works and excerpts were not included. Participants responded to a set of questionnaires measuring trait anxiety, fear of negative evaluation, flow, acceptance, and theatre performance anxiety. Pearson’s correlation coefficient and Multiple Regression Analysis were used to analyze the data. Results revealed that trait anxiety was significantly and positively correlated with theatre performance anxiety (r(203)= .52, p< .001,one-tailed), fear of negative evaluation was significantly and positively correlated with theatre performance anxiety (r(203)= .66, p< .001,one-tailed), flow was significantly and negatively correlated with theatre performance anxiety (r(203)= -.44, p< .001,one-tailed), acceptance was significantly and negatively correlated with theatre performance anxiety (r(203)= -.41, p< .001,one-tailed) When examined together, trait anxiety, fear of negative evaluation, flow and acceptance significantly predicted theatre performance anxiety and account for 50% of its variance (R 2= .50, p<.001)